Green Space, Violence, and Crime: A Systematic Review. (April 2016) - Bogar, Sandra; Beyer, Kirsten M.
Purpose: To determine the state of evidence on relationships among urban green space, violence, and crime in the United States. Methods and Results: Major bibliographic databases were searched for studies meeting inclusion criteria. Additional studies were culled from study references and authors' personal collections. Comparison among studies was limited by variations in study design and measurement and results were mixed. However, more evidence supports the positive impact of green space on violence and crime, indicating great potential for green space to shape health-promoting environments. Conclusion: Numerous factors influence the relationships among green space, crime, and violence. Additional research and standardization among research studies are needed to better understand these relationships.